ANALISIS PERHITUNGAN PPh BADAN DALAM RANGKA PENYESUAIAN UNDANG-UNDANG DAN PERATURAN PAJAK YANG BERLAKU - Hartanti Hartanti (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
The country's biggest source of revenue comes from taxes, one of which comes from income tax on the subject of corporate tax. Corporate taxpayers in their tax obligations must be based on the Tax Act and regulations applicable taxes and carry out the assessment system in the form of bookkeeping self, count, deposit and report his income tax. This study aims to determine the amount of corporate tax under the Act and the applicable tax regulations in 1994 to 2013, while the law used is Act 10 of 1994, Act 17 of 2000, Act 36 of 2008 and Regulation government No. 46 2013. The method used is descriptive qualitative analysis by analyzing and comparing the magnitude of the tax year is based on rates of Law No.10 of 1994, Act 17 of 2000, Act 36 of 2008 and Government Regulation No. 46 in 2013. The data used in the form of financial statements of fiscal PT. HKR that have been through the process of fiscal correction. The research results indicate the magnitude of the corporate tax rate based on Law No.36 of 2008 is lower than the laws and regulations of the previous tax, taxable income to the extent the same amount of each tax year. While PP 46 can not be done due to gross income of more than $ 4.8 billion, so it does not include the criteria imposed PPH final 1%. This means the tax rate imposed on the taxpayer's particular company the lower body, so that the income tax paid by the lower. So hopefully with the lower rates, the level of awareness and tax compliance in implementing the higher tax obligations Key words : Corporate Income Tax, Tax Rate, Constitution and Regulations